Laser soliton microcombs heterogeneously integrated on silicon - Xiang, Chao; Liu, Junqiu; Guo, Joel; Chang, Lin; Wang, Rui Ning; Weng, Wenle; Peters, Jonathan; Xie, Weiqiang; Zhang, Zeyu; Riemensberger, Johann; Selvidge, Jennifer; Kippenberg, Tobias J.; et al. (Science (American Association for the Advancement of Science), 2021)
The realization of optical frequency combs, light sources with precisely spaced frequencies across a broad spectrum of wavelengths, in dielectric microresonators has affected a range of applications from imaging and ranging to precision time keeping and metrology. Xiang et al. demonstrate that the entire system, the laser-pumping system and the comb-generating microresonators, can be combined into an integrated silicon-based platform. Compatibility with foundry fabrication methods will enable this innovation to have a major impact on coherent communications, optical interconnects, and low-noise microwave generation. Science , abh2076, this issue p. 99 Optical microresonator frequency combs are realized in an integrated Si-based platform. Silicon photonics enables wafer-scale integration of optical functionalities on chip. Silicon-based laser frequency combs can provide integrated sources of mutually coherent laser lines for terabit-per-second transceivers, parallel coherent light detection and ranging, or photonics-assisted signal processing. We report heterogeneously integrated laser soliton microcombs combining both indium phospide/silicon (InP/Si) semiconductor lasers and ultralow-loss silicon nitride (Si 3 N 4 ) microresonators on a monolithic silicon substrate. Thousands of devices can be produced from a single wafer by using complementary metal-oxide-semiconductor–compatible techniques. With on-chip electrical control of the laser-microresonator relative optical phase, these devices can output single-soliton microcombs with a 100-gigahertz repetition rate. Furthermore, we observe laser frequency noise reduction due to self-injection locking of the InP/Si laser to the Si 3 N 4 microresonator. Our approach provides a route for large-volume, low-cost manufacturing of narrow-linewidth, chip-based frequency combs for next-generation high-capacity transceivers, data centers, space and mobile platforms.